Developing the "Will": The Relationship between Teachers' Perceived Policy Legitimacy and Instructional Improvement. Issue 3 (March 2019) - Kim, Jihyun; Sun, Min; Youngs, Peter
Background/Context: As part of a nationwide initiative that re-conceptualized teacher evaluation, Virginia issued the Guidelines for Uniform Performance Standards and Evaluation Criteria for Teachers on July 1, 2012; these guidelines marked a significant overhaul of the state's approach to teacher evaluation. Previous studies examined the impact of teacher evaluation policies on student achievement, but there has been little empirical research on factors that lead teachers to change their instructional practices in response to teacher evaluation. Purpose/Objective/Research Question/Focus of Study: We focused on an important element of policy implementation: teachers' perceptions of the legitimacy of teacher evaluation policies. Specifically, we asked: 1) How do teachers' perceptions of the legitimacy of teacher evaluation policies influence their efforts to improve their instruction? and 2) What school supports are associated with an increase in teachers' perceived policy legitimacy? Our examination of teachers' perceived legitimacy of teacher evaluation policies is critically important because individuals' beliefs affect their willingness to respond to externally initiated reform in productive ways and to generate sustainable changes in instruction. Research Design: To examine the potential impact of teachers' perceived legitimacy of teacher evaluation policies on their instruction and the effects of various supports on teachers' perceptions, we drew on teacher survey data and teacher evaluation ratings from two school districts in Virginia. We collected two years of teacher survey data, and three years of teacher evaluation ratings. Combining two different data sets, we provided evidence of an association between teachers' perceived legitimacy of teacher evaluation policies and their instructional practice. Conclusions/Recommendations: Our findings indicate that teachers' perceived legitimacy of evaluation policies is positively correlated with their likelihood of taking actions to improve their instruction. That is, developing teachers' perceptions of policy legitimacy seems to be a fruitful strategy for promoting changes in instruction. Moreover, teachers' perceived legitimacy of teacher evaluation policies seems to have a positive relationship with various school supports, such as principal leadership, professional development, and time and resources. "The consequences of even the best planned, best supported, and most promising policy initiatives depend finally on what happens as individuals throughout the policy system interpret and act on them … Policy success depends critically on two broad factors: local capacity and will." (McLaughlin, 1987, p. 172)